2019
DOI: 10.1080/02670844.2019.1662645
|View full text |Cite
|
Sign up to set email alerts
|

Improving hot corrosion resistance of Cr3C2–20NiCr coatings with CNT reinforcements

Abstract: Carbon Nanotubes (CNT) reinforced Cr 3 C 2 -20NiCr composite coatings were prepared and deposited on alloy steel using high-velocity oxyfuel (HVOF) thermal spraying method. The comparative effects of variation in CNT content (from 1 to 2 weight percentage) on mechanical properties and hot corrosion behaviour in super-heater zone of actual coal-fired boiler of a thermal power plant at 900°C have been investigated. After exposure to boiler environment, the corrosion products have been analysed by thermogravimetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 43 publications
(50 reference statements)
1
8
0
Order By: Relevance
“…The presence of Fe and Mn in the Ni-20Cr conventional coating was found by EDS analysis, which could be attributable to Fe and Mn migration from the substrate to the coating matrix due to porosity in conventional coating. Diffusion of base elements through pores/voids in the coating matrix has also been reported by various authors [32][33][34][35]. Reinforcement of nano YSZ particles in Cr3C2-25NiCr coating filled the gaps, reducing porosity which prevents diffusion of base elements to the coating matrix, thereby increasing the microhardness of the coatings.…”
Section: Vickerssupporting
confidence: 58%
“…The presence of Fe and Mn in the Ni-20Cr conventional coating was found by EDS analysis, which could be attributable to Fe and Mn migration from the substrate to the coating matrix due to porosity in conventional coating. Diffusion of base elements through pores/voids in the coating matrix has also been reported by various authors [32][33][34][35]. Reinforcement of nano YSZ particles in Cr3C2-25NiCr coating filled the gaps, reducing porosity which prevents diffusion of base elements to the coating matrix, thereby increasing the microhardness of the coatings.…”
Section: Vickerssupporting
confidence: 58%
“…CNTs are responsible for reduced porosity and improved adhesion, which further decrease the corrosion rate [7,9]. A number of researchers [15,16] have reported similar findings in their studies on carbon nanotubes.…”
Section: Discussionmentioning
confidence: 71%
“…This ash contains K2O and Na2O and reacts with boilers flue gases (SO2, SO3 and O2). The authors [13][14][15][16] reported that this content of ash was rendered because of coal burning. Deposition of such low melting-point elements initiates hot corrosion on the boiler tube surface [17].…”
Section: Discussionmentioning
confidence: 99%
“…A hot corrosion cycle composed of heating the test specimen for 1-h exposure in the furnace followed by 20 min of cooling to room temperature. The cyclic tests were performed to simulate an actual boiler environment (Goyal, 2018b; Goyal et al , 2017; Rani et al , 2017; Goyal and Goyal, 2020). The weight of each specimen along with the alumina boat was measured carefully on digital weighing machine after every cycle.…”
Section: Experimentation and Methodologymentioning
confidence: 99%